Idiot . The Idiot - Panasenko, Yulia; Strel’nikova, Svetlana (Kinoteatr.Doc, 2007)
Verzio FF Submission The story of Andrei who ran away from a psychiatric hospital, went to Moscow, where without documents and a place to sleep he commutes between the offices of various authorities and endless psychiatric examinations. Earlier having been diagnosed with mental incapability, he is set to become capable again.